ENHANCING THE YIELD OF BARLEY (HORDEUM VULGARE L.) USING CRISPR/CAS TECHNOLOGY: https://doi.org/10.5281/zenodo.15240357 - Turaev , O.S; Sodiqova , M.O.; Ibrohimova , N.M. (International scientific and practical conference, 2025)
This paper provides a review of current and ongoing research focused on increasing barley (Hordeum vulgare L.) yield using CRISPR/Cas technology. Barley is a crucial cereal crop with significant economic and agricultural importance, and improving its yield is essential for addressing food security challenges. Recent studies highlight the potential of CRISPR/Cas gene-editing technology to modify key genes involved in yield improvement, such as HvDEP1, HvGA20ox2, and HvCKX2, which regulate plant architecture, gibberellin biosynthesis, and cytokinin metabolism, respectively. This review discusses the effectiveness of CRISPR/Cas-mediated gene editing in barley, emphasizing different transformation methods, including Agrobacterium-mediated transformation and direct gene editing techniques. The successful applications of genome editing in barley, along with potential future directions, are explored to provide insights into the role of CRISPR-based breeding in improving crop productivity [4].